Living, dying, after death: Achieving a "good" death in the time of AIDS orphan care. Issue 5 (28th May 2018) - Block, Ellen
ABSTRACT: AIDS has devastated communities across southern Africa, leaving many children orphaned. Grandmothers are considered ideal caregivers because of cultural expectations of intergenerational care, and because they have not been decimated by AIDS to the same extent as younger adults. However, these grandmothers, who currently carry the majority of the burden of care for AIDS orphans, are themselves aging and dying. I argue here that in Lesotho, the caregiving demanded of grandmothers late into their lives not only alters kin relations for the living but has increasingly made a "good" death unachievable for elderly caregivers.